2019
DOI: 10.1002/capr.12275
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effectiveness and acceptability of a new technology system to support psychotherapy helping skills training

Abstract: Training counselling and psychotherapy skills using new technology is a relatively unresearched area of study. The findings from a pilot evaluation of the effectiveness and acceptability of a new technology, mPath, using a mixed method design are reported. The study found that progressive integration of the new mPath technology into learning helping skills had the best results on developing competency, as assessed by the Person‐Centred Experiential Psychotherapy Scale Training Version. Qualitative interviews s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 14 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Participants could use the system to record themselves engaging in DP and then send their responses to an MKO for feedback. Similarly, Murphy et al (2020) found that using a software system (mPath) to support students in learning person‐centred skills was best achieved by integrating the system within the curriculum in the university, and that participants found it acceptable. Participants could review their video recordings, reflect on sessions and make annotations on different points of their video, in addition to submitting videos to supervisors for feedback.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Participants could use the system to record themselves engaging in DP and then send their responses to an MKO for feedback. Similarly, Murphy et al (2020) found that using a software system (mPath) to support students in learning person‐centred skills was best achieved by integrating the system within the curriculum in the university, and that participants found it acceptable. Participants could review their video recordings, reflect on sessions and make annotations on different points of their video, in addition to submitting videos to supervisors for feedback.…”
Section: Resultsmentioning
confidence: 98%
“…In this review, DP was applied to the acquisition of skill development in the learning of three different therapeutic modalities: motivational interviewing, person‐centred therapy and problem‐solving therapy, in four studies (Barrett‐Naylor et al, 2020; Di Bartolomeo et al, 2021; Murphy et al, 2020; Westra et al, 2021). Two of these studies had active controls, and the DP intervention fared better in the development of competencies in learning skills and on subsequent outcomes for managing ambivalence and resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mPath is designed for developing learners’ interpersonal skills during off-training moments. It allows learners to gather their annotations and affective responses to video-recorded skills practice sessions in either a textual form or a graphic format, facilitating self-reflection, and to request and respond to peer feedback on the recorded practice sessions [ 20 , 21 , 34 , 36 ]. However, how the participants develop skills with mPath and which features enhance learns knowledge remain unexplored.…”
Section: Methodsmentioning
confidence: 99%
“…Rogers and Barrett-Lennard also emphasised that facilitating a specific learning environment can enhance the trainees’ personal and training experience in learning [ 2 , 8 , 18 ]. Medical educators should develop effective courses for learning communicational skills online, which would successfully maintain and enhance the learning outcome for health-care students [ 19 , 20 ]. Liao and Murphy reported continual growth of communication skills ability, with skills abilities continuing to develop after the class-based training with lectures, group discussions, and the use of online technology had ended [ 18 ].…”
Section: Introductionmentioning
confidence: 99%